Infancias y trabajo: vivencias y construcción de subjetividades en niños y adolescentes recicladores de la parroquia Guanujo, 2023. - Chiliquinga Mena Katherine Giessella (2025)
The objective of this research is to analyze the experiences and create subjectivities in the lives of boys, girls and adolescents who work as recyclers within the parish of Guanujo belonging to the Guaranda Canton. Subsequently, it analyzes from a Sociological perspective in addition to being able to know in depth the various causes that promote child labor. The research is handled with a qualitative approach using the metaphor as a tool that starts from the collection of information based on images that will be applied to the children and adolescents who live in the Guanujo parish who carry out the work of recyclers with this activity it will be evident. the work of boys and girls and adolescents, the time they use to carry out this activity is greater than the time they dedicate to studies, play, food, rest, and the different risks and dangers to which they are exposed and which are also detailed. seriously harm your health. This situation of child labor in the recycling field is considered one of the worst forms of work in which their rights are violated. In this research work, information is obtained through the metaphor that tries to reach the experiences and subjectivities of children and adolescents through drawings that they capture on paper and at the same time with games that help to have a better response on the part of the children. participants. The objective of this research is to analyze the experiences and subjectivities of children and adolescents who work in the recycling area, collecting information through a new and very little-known tool such as metaphor. This technique is based on obtaining information through dynamics. like the game, the drawing captured on paper and figures made in plasticine, this tool is very useful because this work collects information in boys and girls between the ages of 5 and 12, in this age period it can be said that it is It is a little difficult to obtain information due to age. With this, you can learn about the experiences that waste picker children go through every day. Keywords: recycling, child labor, health, risks, work, experiences, subjectivities